El teatro musical en Buenos Aires : II. Teatro Coliseo 1907-1937 ; 1961-1998 / César A. Dillon y Juan A. Sala. Buenos Aires : Gaglianone, 1999. xvi, 495 p. : il. ISBN 950-720-067-3 (Información, cultura y sociedad, 2004)
Reseña.